2003
DOI: 10.1002/cncr.11645
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy alone or after subtotal resection for benign skull base meningiomas

Abstract: In 18 fluoropolymers with different repeating‐unit structures and crystallinities, the solubility, diffusivity, and permeability at 70°C of a polarizable nonpolar solute (tetrachloroethylene) were studied. The transport properties were mostly controlled by the polarity of the polymer and to a lesser degree by the polymer crystallinity. The highest permeability was observed in the dipole‐containing ethylene–chlorotrifluoroethylenes because of their high tetrachloroethylene solubility. The lowest permeability wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 37 publications
1
62
0
1
Order By: Relevance
“…Progression-free survival rates at 5 and 10 years after conventional radiotherapy range from 73% to 92% and 61% to 83%, respectively. 23,25,26,35,40,57 More contemporary techniques such as intensity-modulated radiation therapy and proton therapy offer increased conformality and more sparing of critical structures compared with conventional techniques. 44,58 The lower integral dose and higher conformality that are touted as the advantages of intensity-modulated radiation therapy and proton beam over conventional radiotherapy techniques for meningiomas have been longstanding features of radiosurgery.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Progression-free survival rates at 5 and 10 years after conventional radiotherapy range from 73% to 92% and 61% to 83%, respectively. 23,25,26,35,40,57 More contemporary techniques such as intensity-modulated radiation therapy and proton therapy offer increased conformality and more sparing of critical structures compared with conventional techniques. 44,58 The lower integral dose and higher conformality that are touted as the advantages of intensity-modulated radiation therapy and proton beam over conventional radiotherapy techniques for meningiomas have been longstanding features of radiosurgery.…”
Section: Radiation Therapymentioning
confidence: 99%
“…External-beam radiation therapy 2,11,32,35,36,38,53,55 as well as stereotactic radiosurgery [3][4][5][6]12,14,[16][17][18][19][20]22,26,27,30,31,33,34,37,40,41,[43][44][45][46]48,54,58,60,61,63,64 have become viable adjuvant treatment as well as primary treatment modalities for many meningiomas. Their use is supported by high rates of tumor control and a low incidence of complications.…”
mentioning
confidence: 99%
“…[28][29][30] As more conformal therapies were developed, higher radiation doses could be administered while sparing dose to surrounding neural structures, resulting in an additional improvement in the 10-year progression-free survival rate. In a more recent study, Mendenhall et al 31 have shown five-, 10-, and 15-year local control rates of 95, 92, and 92%, respectively, for meningiomas treated with radiation therapy subsequent to subtotal resection.…”
Section: Radiosurgical Treatmentmentioning
confidence: 96%
“…25,[33][34][35] The efficacy of this method is clearly demonstrated by radiosurgical control rates, which have been reported to be extremely high: approaching or exceeding 90% in many contemporary studies involving either linear accelerator-based systems or gamma knife surgery (GKS). 2,3,25,31,[36][37][38][39][40][41] The efficacy of stereotatic radiosurgery as an alternative to aggressive resection was confirmed in a recent study published by Davidson et al 42 They found that for those patients treated with GKS with an initial subtotal resection or with recurrent disease, the five-and 10-year actuarial progression-free survival rate was 100 and 94%, respectively.…”
Section: Radiosurgical Treatmentmentioning
confidence: 99%